Handbook of research on digital communications, Internet of Things, and the future of cultural tourism - Oliveira, Lidia (IGI Global, 2022)
"This book is aimed at researchers who want to improve their understanding of the strategic role of new digital technologies in the field of cultural tourism, offering innovative research results within the scope of the interdisciplinary cross between Digital Communications, Internet of Things, and Cultural Tourism